Cathode design and gap multi-physical field coupling simulation analysis for ECM of shaped grid holes - Wang, Yajun; Jia, Jianli; Song, Mei; Hao, Yajing (International journal of advanced manufacturing technology, 2024)
In this paper, a study was conducted on the electrochemical machining (ECM) of titanium-shaped grid holes. Firstly, the polarization characteristic curves of titanium alloy TC4 in different electrolytes were measured by an electrochemical workstation, and the mechanism of action was analyzed. The electrolyte formula was developed for 11%NaCl + 5%NaNO 3 saturated ethylenediaminetetraacetic acid (EDTA). Secondly, the equal clearance method was used to design the cathode, gap flow field simulation was used to analyze five different structures of through-liquid slots, and the structural form and size of the through-liquid slots were preferred. The voltage range of ECM was determined to be 14 ~ 22 V by the multi-physical field coupling simulation analysis. Finally, through the process test, the Taguchi algorithm and gray correlation degree method were used to optimize the process objectives; to obtain the degree of influence of different factors on the experimental process objectives, machining voltage > feed velocity > duty ratio > inlet pressure; and to obtain the optimal combination of machining parameters, machining voltage of 20 V, duty ratio of 35%, inlet pressure of 0.7 MPa, and feed velocity of 0.55 mm/min. The titanium-shaped grid holes machined by the optimal process parameters have a dimension error of 0.14 mm and a surface roughness of 0.812 μm, which meet the actual production requirements. Using this process parameter for ECM of the more difficult shaped blind holes (hole depth of 10 mm), the dimension error and roughness meet the processing requirements, which further verifies the feasibility of the optimal parameters. The research results show the ECM can realize high-efficiency and high-quality processing of the titanium-shaped grid hole. It also provides process technology reference for the machining of other complex-shaped hole parts to promote the technical progress of the industry.